Thermal Based Exploration for Search and Rescue Robots - Cakmak, Furkan; Uslu, Erkan; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2017)
Detection of thermal targets for search and rescue robots is very important to be able to save more lives. Because the living human body is at a certain temperature, each thermal target point implies possible victim. Robots produced for search and rescue are expected to be able to perceive and steer toward the thermal targets. The focus of this work, which is also a criterion of RoboCup competitions, is the development of an exploration method for the determination of thermal targets. An algorithm has been developed which relies on giving travel priority to the thermal information emitting targets in the environment. So that the victims can be detected more effectively. Additional methodsg, such as human detection from image processing, detecting carbon dioxide gas, motion detection, etc., can be used to identify the victim, in consideration of the fact that every thermal target in the environment may not be human bein This study only involves detecting thermal targets and directing the mobile robots to them. Successful results are ensured by making the method more stable thanks to tests in both the real environment and the simulation environment. Gazebo is used as the simulation environment, and a differential drive mobile robot with a thermal camera is used for real environment experiments. Since there is no thermal camera in Gazebo simulation environment, a system was designed to represent thermal targets. This system is based on obtaining representative thermal images by applying various filters to normal camera images.
Keywords: thermal-based exploration; search and rescue robots; ROS; exploration; Computer Science